Association of Nurse Engagement and Nurse Staffing on Patient Safety. Issue 1 (January 2019) - Brooks Carthon, J. Margo; Hatfield, Linda; Plover, Colin; Dierkes, Andrew; Davis, Lawrence; Hedgeland, Taylor; Sanders, Anne Marie; Visco, Frank; Holland, Sara; Ballinghoff, Jim; Del Guidice, Mary; Aiken, Linda H.
Abstract : Background: Nurse engagement is a modifiable element of the work environment and has shown promise as a potential safety intervention. Purpose: Our study examined the relationship between the level of engagement, staffing, and assessments of patient safety among nurses working in hospital settings. Methods: A secondary analysis of linked cross-sectional data was conducted using survey data of 26 960 nurses across 599 hospitals in 4 states. Logistic regression models were used to examine the association between nurse engagement, staffing, and nurse assessments of patient safety. Results: Thirty-two percent of nurses gave their hospital a poor or failing patient safety grade. In 25% of hospitals, nurses fell in the least or only somewhat engaged categories. A 1-unit increase in engagement lowered the odds of an unfavorable safety grade by 29% ( P < .001). Hospitals where nurses reported higher levels of engagement were 19% ( P < .001) less likely to report that mistakes were held against them. Nurses in poorly staffed hospitals were 6% more likely to report that important information about patients "fell through the cracks" when transferring patients across units ( P < .001). Conclusions: Interventions to improve nurse engagement and adequate staffing serve as strategies to improve patient safety. Abstract : Supplemental Digital Content is Available in the Text.